Handbook of system safety and security : cyber risk and risk management, cyber security, threat analysis, functional safety, software systems, and cyber physical systems /: cyber risk and risk management, cyber security, threat analysis, functional safety, software systems, and cyber physical systems. (2016) - Unknown
No abstract available